Methods of Differentiating Color Painting Lessons in Fine Arts Classes - Abdurahmonova Dildora Nizomjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores methods for differentiating color painting lessons in fine arts classes to address the diverse abilities and learning styles of students. It highlights pedagogical strategies that enhance students’ creative thinking, visual perception, and mastery of color and composition. Differentiated instruction, practical exercises, and project-based learning are emphasized as effective approaches to engage all students, foster independent artistic activity, and develop individual potential in visual arts education.